The Palgrave Handbook of Gender and Healthcare
XXIII, 535 p.
Keywords: An authoritative, state-of-the-art collection that brings together key experts to provide an overview of the field. This new paperback edition includes 3 new chapters on human resources and health, end-of-life care and complementary and alternative medicine as well as thorough updates to the introduction and conclusion.